IMPLEMENTATION OF CAPITAL OWNERSHIP, DIGITAL PAYMENT AND DIGITAL SALES TOWARDS MSME BUSINESS SUSTANABILITY IN BANGKA BELITUNG - Fahry Reza; Ersi Sisdianto (JURNAL ILMIAH EDUNOMIKA, 2024)
The problems faced in the affairs of cooperatives, Small and Medium Enterprises are quite complex, apart from the quality of human resources, capital, payment media, product marketing problems, raw materials and infrastructure are the main obstacles in the development of the Cooperative and MSME sectors. From a marketing perspective, MSME products are less well known due to the lack of promotion and marketing, as well as less than optimal use of digitalization in introducing MSME products or work at both the national and international levels. The aim of this research is to determine and analyze the influence of capital ownership, digital payments and digital sales on the sustainability of MSME businesses in Bangka Belitung Province. The population and sample size in this research is 60 MSME actors spread across Bangka Belitung Province. The sampling technique determined is purposive sampling. and data processing tools, namely SPSS 25. The research results show that the capital ownership variable has a significant positive influence on the sustainability of MSME businesses, the digital payment variable has a positive but not significant influence on the sustainability of MSME businesses while the digital sales variable has a positive but not significant influence. not significant to the sustainability of MSME businesses. It is hoped that the implications of this research will be useful for MSME business actors and look at how to maintain the sustainability of MSME businesses and for future researchers it is hoped that they can add other variables or objects of analysis to make a wider population and sample. Keywords: Digital Payments, Digital Sales, Sustainability Business, MSMEs